SIMULASI DAN ANALISIS ANTENA UWB TRISULA 2,4 GHZ MENGGUNAKAN ANSOFT HFSS 13 - Sonalitha, S.Kom.,M.T., Elta; Fachrurizal, Andry; Alwan, Chotib; Akramul, Busro; Zamroni, Subhan (Universitas Merdeka Malang, 2015)
Simulating trident-shaped UWB antenna using Ansoft software 13. HFSS simulation was conducted to determine the parameters - the antenna parameters, namely : VSWR, return loss and axial ratio. After the simulation is done and the results of the measurements parameters - the parameters of the antenna, it will be described as well like creating / fabricating antenna using a simple manner. Antennas are already in - fabrication will certainly be able to was measured using a measuring instrument that is in fact, not a simulation